Portaria PRCE n° 700, de 19 de dezembro de 2016 - (:unkn) unknown (DMPFe, Administrativo de 20/12/2016, p. 26., 2016)
Altera, parcialmente, o artigo 1º da Portaria Gab/Chefia nº 683, de 16 de dezembro de 2016.